2021
DOI: 10.3390/healthcare9091111
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Characteristics and Usefulness of User Reviews of Online Mental Health Consultation Services: A Content Analysis

Abstract: Online consultation based on Internet technology is gradually becoming the main way to seek health information and professional assistance. Online user reviews, such as content reviews and star ratings, are an important basis for reflecting users’ views on the effectiveness of health services. Here, we used user reviews related to online psychological consultation services for content feature mining and usefulness analyses. We used a professional online psychological counseling service platform in China to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The lexicon is a list of words, each associated with corresponding emotions (anger, fear, anticipation, trust, surprise, sadness, joy, and disgust) and sentiments (positive and negative); this classification is in line with the work of Plutchik and his wheel of emotions [ 22 ]. The NRC lexicon has been increasingly applied in recent years for quantifying affect in online textual data [ 23 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lexicon is a list of words, each associated with corresponding emotions (anger, fear, anticipation, trust, surprise, sadness, joy, and disgust) and sentiments (positive and negative); this classification is in line with the work of Plutchik and his wheel of emotions [ 22 ]. The NRC lexicon has been increasingly applied in recent years for quantifying affect in online textual data [ 23 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Brzustewicz P et al [16] used LDA for topic modeling and the Louvain algorithm for semantic network clustering to analyze sustainable consumption during the COVID-19 pandemic. Liu J et al [17] used LDA topic modeling, dictionary-based sentiment analysis and the NRC Word-Emotion Association Lexicon to extract the topics, sentiments and context features of user reviews of online mental health consultation services. Zhang N et al [18] crawled online reviews of express companies and used an LDA model and sentiment analysis to identify service attributes and customer satisfaction so as to analyze user-generated content and provide a scientific service innovation scheme for express enterprises.…”
Section: Text Feature Extractionmentioning
confidence: 99%
“…Sentiment analysis is a machine learning-based technique for rating positive or negative use of language in text that recently led to an increased understanding of clinical contributors to patient satisfaction in surgical fields (10,11). In the field of psychiatry, previous studies have demonstrated the validity of sentiment analysis among antidepressant users and for online mental health consultation services (12,13). Specifically, while the general attitude toward online mental health consultation services and the usefulness of online reviews in China have previously been examined, no studies to date have elucidated impactful attributes of psychiatrists that can improve patient experiences during their mental health visits in the United States using PRWs (13).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of psychiatry, previous studies have demonstrated the validity of sentiment analysis among antidepressant users and for online mental health consultation services (12,13). Specifically, while the general attitude toward online mental health consultation services and the usefulness of online reviews in China have previously been examined, no studies to date have elucidated impactful attributes of psychiatrists that can improve patient experiences during their mental health visits in the United States using PRWs (13). To that end, the present study aimed to utilize sentiment analysis on online written reviews of psychiatrists from PRWs to identify demographic and clinical characteristics strongly associated with reviews with the most positive and negative sentiment.…”
Section: Introductionmentioning
confidence: 99%